Evaluation of Cytotoxic T-Lymphocyte Antigen 4 Polymorphism and Soluble Immune Checkpoint Level Among A Sample of Sars-Cov-2 Iraqi Patients - Anmar Layth Talib, Haider Sabah Kadhim, Amar Kasim Muhammed, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To Evaluate the Roley of Cytotoxic T-Lymphocytek antigen 4 Polymorphism and soluble immune checkpoint level (PD-1,PDL-1 and CTLA-4 ) in SARS-Cov-2 patients. Methods: Fromt October 2020 to April 2021, the currentk study was conducted in Baghdad-Iraq. Ninety patients with Confirmatory SARS-Cov-2 by PCR were inclusion in the study, and they were seeking treatment at Medical City in Baghdad's Teaching Hospital (BTH). Patients with SARS-Cov-2 were divided into two groups: those with Sever SARS-Cov-2 symptom and those with mild - moderate SARS-Cov-2 symptoms (cross sectional study. Patients with another form of autoimmune illness, malignant, diabetes, under the age of 18 and pregnant women were excluded. Results: Data regarding serum level of CTLA-4f, PD-1j and PD-L1 in mild-moderate and severe covid19 patients were found to be non-normally distributed. The median serum level of CTLA-4, PD-1 and PD-L1 mild-moderate groups were much lower than that of severe cases with highly significant differences. Age demonstrated a positive significant correlation with each of CTLA-4 (r= 0.281, p= 0.007), PD-1 (r= 0.282, p= 0.007) and PD-L1 (r= 0.219, p= 0.039). Soluble CTLA-4 had a positive significant correlation with each of PD-1 (r=0.714, p<0.001) and PD-L1 (r= 0.602, p<0.001). Allele specific of CTLA-4(+49G/A) PCR was used for gene amplification and genotyping under Gel electrophoresis of PCR products revealed that this SNP had three genotypes in mild/moderate and severe cases of COVID-19. These were GG, GA and AA. The wild homozygous genotype (AA) was more frequent among severe group than mild-moderate group with a significant difference. Conclusion: Soluble Immune checkpoint markers are significantly increased in patients with covoid-19 in severe cases and soluble immune checkpoint markers are positively significant correlation with age and The genotyping CTLA-4(+49G/A) gene SNP (AG and GG by allele specific PCR) was significantly higher in mild-moderate covid-19 cases in which may indicate that this SNP mostly protective with good prognosis.